Speech by Mr. Károly Kiss at the Mass Meeting in Varna, Bulgaria - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. The Verdict of the Supreme Court in connection with the trial of the traitor Imre Nagy and his associates was severe but just. Based on information from Népszabadság.